Baseline characteristics and risk factors for ulcer, amputation and severe neuropathy in diabetic foot at risk: The BRAZUPA study - Parisi, Maria Candida R.; Neto, Arnaldo Moura; Menezes, Fabio H.; Gomes, Marilia Brito; Teixeira, Rodrigo Martins; De Oliveira, José Egídio Paulo; Pereira, Joana Rodrigues Dantas; Fonseca, Reine Marie Chaves; Guedes, Lorena Barreto Arruda; E Forti, Adriana Costa; De Oliveira, Ana Mayra Andrade; De Medeiros Nóbrega, Marta Barreto; et al. (Springer Nature, 2016)
Background: Studies on diabetic foot and its complications involving a significant and representative sample of patients in South American countries are scarce. The main objective of this study was to acquire clinical and epidemiological data on a large cohort of diabetic patients from 19 centers from Brazil and focus on factors that could be associated with the risk of ulcer and amputation. Methods: This study presents cross sectional, baseline results of the BRAZUPA Study. A total of 1455 patients were included. Parameters recorded included age, gender, ethnicity, diabetes and comorbidity-related records, previous ulcer or amputation, clinical symptomatic score, foot classification and microvascular complications. Results: Patients with ulcer had longer disease duration (17.2 ± 9.9 vs. 13.2 ± 9.4 years; p < 0.001), and poorer glycemic control (HbA1c 9.23 ± 2.03 vs. 8.35 ± 1.99; p < 0.001). Independent risk factors for ulcer were male gender (OR 1.71; 95 % CI 1.2-3.7), smoking (OR 1.78; 95 % CI 1.09-2.89), neuroischemic foot (OR 20.34; 95 % CI 9.31-44.38), region of origin (higher risk for those from developed regions, OR 2.39; 95 % CI 1.47-3.87), presence of retinopathy (OR 1.68; 95 % CI 1.08-2.62) and absence of vibratory sensation (OR 7.95; 95 % CI 4.65-13.59). Risk factors for amputation were male gender (OR 2.12; 95 % CI 1.2-3.73), type 2 diabetes (OR 3.33; 95 % CI 1.01-11.1), foot at risk classification (higher risk for ischemic foot, OR 19.63; 95 % CI 3.43-112.5), hypertension (lower risk, OR 0.3; 95 % CI 0.14-0.63), region of origin (South/Southeast, OR 2.2; 95 % CI 1.1-4.42), previous history of ulcer (OR 9.66; 95 % CI 4.67-19.98) and altered vibratory sensation (OR 3.46; 95 % CI 1.64-7.33). There was no association between either outcome and ethnicity. Conclusions: Ulcer and amputation rates were high. Age at presentation was low and patients with ulcer presented a higher prevalence of neuropathy compared to ischemic foot at risk. Ischemic disease was more associated with amputations. Ethnical differences were not of great importance in a miscegenated population.
Keywords: Amputation; Brazil; Diabetes; Risk factors for ulcer; Severe neuropathy